LAND OF FOOD AND SPAS - Gulan, Branislav; Stanković, Vojislav (Economics of Agriculture, 2011)
About 20 million t of agricultural products in the value of 5.5 billion dolar produced annually in Serbia on arable land area of 4.1 million ha. In 2010, the food was exported in the value of 2 billion dollars (which makes one ffth of total Serbian exports), while in the imports stood at 2.2 billion dollars. The surplus amounted to 1,2 million dollars. Bigger food production and its realization with support to stronger rural tourism development could be realized with the investment of about one billion euro and the entire region be proclaimed as an area without genetically modifed products. This is very important because 10% of EU inhabitants, or about 50 million people said that they want to consume such kind of food. Serbia could attract a signifcant number of visitors thanks to branded food and rural tourism (about 1000 events are organized annually). Serbia has a great potentials when it comes to rural and spa tourism. Serbia disposes of 40 spas and about 400 mineral or thermal mineral water springs. In line with this abundance in mineral waters, Serbia could be called "a land of spas".